Comparison of Left Ventricular Global Strain in Anterior and Non-anterior Wall Myocardial Infarction With CMR Tissue Tracking - Li, Shuhao; Zhao, Lei; Lu, Aijia; Tian, Jie; Gong, Lianggeng; Ma, Xiaohai (Frontiers in Physiology, 2020)
Left ventricular (LV) myocardial dysfunction that occurs after myocardial infarction (MI) is associated with the location, infarct size, and transmurality degrees of MI. The myocardial strain is a sensitive index used for the quantification of myocardium dysfunction. This study used Tissue-Tracking to evaluate whether the different location of MI would result in different myocardial dysfunction. 100 patients diagnosed with MI who underwent cardiovascular magnetic resonance examination were included. The tissue-tracking indexes, LV global radial strain (GRS), global circumferential strain (GCS), global longitudinal strain (GLS), and the infarct size (IS, % of LV mass) were quantified. There were 42 cases of anterior wall MI (AWMI) and 58 cases of non-anterior wall MI (NAWMI). The GCS of AWMI was significantly lower than that of NAWMI (P=0.036). In the same level of infarct size, the strain of AWMI was not significantly different to NAWMI group (P>0.05), the GRS and GCS were significantly different between transmurality>50% group with transmurality≤50% group (P<0.05). The present study demonstrated that LV MI is associated with reduced myocardial strain, and the infarct size and degrees of transmurality are both related to the decline of strain in patients with MI.